An evaluation of gemcitabines differential radiosensitising effect in related bladder cancer cell lines - Sangar, V K (Nature Publishing Group, 2004)
The aim of this study was to establish the radiosensitising properties of gemcitabine in a pair of related bladder tumour cell lines with differential radiosensitivity. The radioresistant bladder tumour cell line MGH-U1 and its radiosensitive mutant clone, S40b (both p53 mutant), had SF(2) values (surviving fraction at 2 Gy) of 0.98 and 0.64, respectively (P<0.001). Colony-forming assays showed that at 0.01 μM gemcitabine radiosensitisation occurred only in the S40b cell line (dose-modifying factor (DMF)=1.4). At 0.3 μM (killing 50% of cells), both cell lines were radiosensitised; DMF=2.25 and 1.2 for MGH-U1 and S40b, respectively. These data suggest that gemcitabine is an effective radiosensitiser in bladder cancer cell lines, with greater sensitisation in the radioresistant parental line–a feature that should be useful in a clinical setting.